Cervical aspergillosis in a post-menopausal female: a case report - Natekar, Ashwini; Basu, Shubasis; Mondal, Gautam; Pujari, Maruti (International Journal of Research in Medical Sciences, 2018)
Fungal infections are commonly encountered in the female genital tract on routine cervical smear examination, the most common being candida. Cervico-vaginal aspergillosis infection is rarely reported. We report a case of aspergillus infection in an immunocompetent 55-year-old post-menopausal female who presented with white discharge per vaginum. Initially the cervical pap smears showed only inflammatory changes. On per speculum examination the cervix appeared congested and ulcerated. Cervical biopsy was performed which showed sheets and balls of aspergillus fungus with areas of necrosis. PAS staining further confirmed the diagnosis. Serological tests performed were negative. Patient was started on antifungal and repeat biopsy from cervix did not show any fungal hyphae.